Feeding difficulties in craniofacial microsomia: a systematic review. Issue 6 (June 2015) - Caron, C.J.J.M.; Pluijmers, B.I.; Joosten, K.F.M.; Mathijssen, I.M.J.; van der Schroeff, M.P.; Dunaway, D.J.; Wolvius, E.B.; Koudstaal, M.J.
Abstract Patients with craniofacial microsomia are at higher risk of developing obstructive sleep apnoea (OSA), as described in the previous article entitled "Obstructive sleep apnoea in craniofacial microsomia: a systematic review". These patients are also more likely to develop feeding difficulties. The present systematic review provides an overview of the literature on the prevalence, treatment, and follow-up of feeding difficulties in children with craniofacial microsomia (CFM). A search was performed in PubMed, Embase, Cochrane Library, and Web of Science for articles on CFM and feeding difficulties. The following data were extracted from the articles: number of patients, patient characteristics, presence of feeding difficulties, and the treatment and outcomes of feeding difficulties. Eight articles on CFM and feeding difficulties were included, two of which reported the prevalence of feeding difficulties (range 42–83%). Treatment mostly consisted of tube feeding. No information regarding follow-up was found in these articles. According to the literature, feeding difficulties are related to CFM. However, as there have been no prospective studies and few studies have presented objective measurements, no definitive conclusions can be drawn. Prospective studies are needed to determine the prevalence of feeding difficulties in patients with CFM.